Dark & twisted : the killing hole - Niles, Steve; Kane, Sandy (Storm King Comics, 2024)
"The Killing Hole is a Gen X coming-of-age drama turned upside-down. Set in 1979 in an isolated planned community of Northern Virginia, 14-year-old Stewart is a lonely and neglected child of divorce. Living in a shabby apartment with his alcoholic working mother (and always absent older sister), he languishes in school, side-stepping bullies and cliques. He notices a new kid at school, Peter, who has it even worse than he does, and the two begin to form an inseparable bond in their mutual hatred of everyone and everything else, especially the worst of all the bullies, the local drug dealer, David Hayes. But as their friendship deepens, things take a very dark turn." -- Amazon.